Use of Robotics in Colon and Rectal Surgery - Pucci, Michael J.; Beekley, Alec C. (Clinics in Colon and Rectal Surgery, 2013)
The pace of innovation in the field of surgery continues to accelerate. As new technologies are developed in combination with industry and clinicians, specialized patient care improves. In the field of colon and rectal surgery, robotic systems offer clinicians many alternative ways to care for patients. From having the ability to round remotely to improved visualization and dissection in the operating room, robotic assistance can greatly benefit clinical outcomes. Although the field of robotics in surgery is still in its infancy, many groups are actively investigating technologies that will assist clinicians in caring for their patients. As these technologies evolve, surgeons will continue to find new and innovative ways to utilize the systems for improved patient care and comfort.
Keywords: robotics; colorectal surgery; robotic-assisted surgery